2004
DOI: 10.1029/2004gb002249
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for warming‐induced growth decline at elevational tree line in the Yukon Territory, Canada

Abstract: A few tree ring studies indicate recent growth declines at northern latitudes. The precise causes are not well understood. Here we identify a temperature threshold for decline in a tree ring record from a well‐established temperature‐sensitive site at elevational tree line in northwestern Canada. The positive ring width/temperature relationship has weakened such that a pre‐1965 linear model systematically overpredicts tree ring widths from 1965 to 1999. A nonlinear model shows an inverted U‐shaped relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
195
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(223 citation statements)
references
References 50 publications
26
195
0
2
Order By: Relevance
“…The Palmer Drought Severity Index (PDSI), which is defined from a water-balance model forced with climate data, shows a significant increase in drought over the NH in the last several decades, and particularly in southern Europe and eastern Asia and Siberia 9 . Increased drought stress can modify the response of plant growth to temperature change 7 and was hypothesized to be a potential cause for the declined temperature sensitivity of tree growth in tree rings time series during the last part of the twentieth century 10 . The effect of climate drought on the temperature sensitivity of vegetation growth, however, may be partly alleviated by CO 2 -induced increase in vegetation water use efficiency 11,12 .…”
mentioning
confidence: 99%
“…The Palmer Drought Severity Index (PDSI), which is defined from a water-balance model forced with climate data, shows a significant increase in drought over the NH in the last several decades, and particularly in southern Europe and eastern Asia and Siberia 9 . Increased drought stress can modify the response of plant growth to temperature change 7 and was hypothesized to be a potential cause for the declined temperature sensitivity of tree growth in tree rings time series during the last part of the twentieth century 10 . The effect of climate drought on the temperature sensitivity of vegetation growth, however, may be partly alleviated by CO 2 -induced increase in vegetation water use efficiency 11,12 .…”
mentioning
confidence: 99%
“…These findings emphasize how the same climatic conditions drive nonproportional variations in glaciers' mass variations and tree-ring growth, especially in the years when extreme meteorological conditions induce strong variations. The different responses to climate could be related to the fact that these two climatic proxies respond to common but also different climate variables and to the fact that high-altitude trees have threshold temperatures above which they may not respond linearly (D'Arrigo et al, 2004). In particular, we found that tree rings mainly responded to July temperature and glacier mass balance to JJA temperature (Figs.…”
Section: Discussionmentioning
confidence: 59%
“…4). Warm temperatures during the growing season may induce moisture stress and decrease tree growth (Barber et al, 2000;D'Arrigo et al, 2004;Miyamoto et al, 2010;Aakala and Kuuluvainen, 2011). High temperatures increase evapotranspiration from soils and plant tissues, inducing stomatal closure and a decreased net photosynthesis to minimize water losses in response to an increasing moisture stress (Kozlowski, 2002).…”
Section: Discussionmentioning
confidence: 99%